Development of virtual kinetics chemistry for the prediction of ignition delay time of a fuel presenting negative temperature coefficient behavior - Pacheco, Augusto Finger (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2022.